Factors Affecting Supply Chain in Al-Wefag Food Company - Bayashot, Mohammed Abdullah Karama (IJRDO - Journal of Business Management, 2019)
The purpose of this research is to investigate the effect of Three different factors in supply chain on alwefag food company’s’ performance. The research initially reviews previous studies conducted on this topic and based on these literatures, the research methodology is designed. The hypotheses of the research paper indicate the relationship between the selected variables and food manufacturing companies’ performance. The independent variables are time Response, information Feasibility, and flexibility. To examine the theoretical and hypotheses of the research, a questionnaire was conducted. The gathered data from the survey had been evaluated by applying SPSS technique findings are presented and discussed to support the research hypotheses and help to manage the selected factors in order to obtain better results in companies.